Conquest of the waters - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc., 1981)
Naturalist Richard Attenborough traces the evolution of marine vertebrates from the sea squirts, through primitive jawless fish, to the cartilagenous sharks and rays, and finally to the bony fish
Keywords: Fishes -- Evolution; Vertebrates -- Evolution; Marine fauna -- Evolution